Mesozooplankton Community Composition Controls Fecal Pellet Flux and Remineralization Depth in the Southern Ocean - Liszka, Cecilia M.; Manno, Clara; Stowasser, Gabriele; Robinson, Carol; Tarling, Geraint A. (Frontiers in Marine Science, 2019)
Zooplankton faecal pellets (FPs) are important conduits of carbon from the surface to the deep ocean, as shown by their presence in deep-sea sediment traps. Zooplankton themselves are thought to play an important role in the breakdown and reworking of FPs as they sink, whilst processes such as diel vertical migration (DVM) may enhance the supply of carbon to the mesopelagic. However, comparatively little is known about the processes or variability of FP sinking/ transport within the upper mesopelagic and how this relates to deeper ocean export. Profiles of FP type and size, and the contribution made by FPs to mesopelagic carbon flux to a depth of 400 m, were considered. Three contrasting locations in the Scotia Sea were compared, which together reflect the variability in physical regime and productivity encountered across the Southern Ocean. Comparing observed FPs with predictions from the mesozooplankton community, we show that, even at shallow depths, the smallest fraction of FP is under-represented, suggesting rapid remineralisation, incorporation into larger aggregates or reworking into larger FPs, and that the flux is dominated by FPs from larger zooplankton. In contrast to models where POC attenuation rates are set to increase with temperature, we find that FP carbon flux attenuates rapidly in low productivity, colder regions dominated by krill, while remineralisation is deeper in warmer areas where productivity is high and copepods dominate. This emphasises the strong modulation of the zooplankton community on the supply and transfer of FP carbon between the epi- and mesopelagic. Evidence was found to suggest that DVM enhances FP flux across the upper mesopelagic, producing a pulse of fresh, dense material that may support secondary production and heterotrophic respiration in the mesopelagic. This illustrates that variability in flux at short (daily) as well as longer (seasonal) timescales may have important implications for the supply of FP carbon to deeper waters.